1994
DOI: 10.1111/j.1399-0004.1994.tb04008.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in the occurrence of the M1(ala213) haplotype of alpha‐1‐antitrypsin in asthmatic and non‐asthmatic black and white South Africans

Abstract: An ethnic study of 175 individuals, comprising 65 black and 110 white South Africans, has shown a conclusive difference in the frequency of the M1(ala213) haplotype of α1‐antitrypsin (P < 0.00001). The M1(ala213) haplotype occurred more frequently in the black group. In the latter group, the frequency of the M1(ala213) haplotype was the same in both controls (0.55) and asthmatics (0.53). However, there was a significant difference in the frequencies (0.19 and 0.36) for the respective white groups (P < 0.01), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The mechanism responsible for the association of the M2 allele with the risk of COPD remains to be elucidated. However, it has been observed that the M2 variant has lower elastase inhibitory capacity compared to the M1 Val variant 13,14 . Therefore, it is possible that individuals with the M2 variant have lower elastase inhibitory capacity, and are thus prone to develop COPD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mechanism responsible for the association of the M2 allele with the risk of COPD remains to be elucidated. However, it has been observed that the M2 variant has lower elastase inhibitory capacity compared to the M1 Val variant 13,14 . Therefore, it is possible that individuals with the M2 variant have lower elastase inhibitory capacity, and are thus prone to develop COPD.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies 7,8,26 , the AAT phenotype was only determined by isoelectric focusing of serum and the serum AAT levels without measuring functional activity of the AAT protein. Although the M2 variant does not affect serum AAT levels, it may alter the functional activity of the AAT protein 13,14 , and thus predispose to the development of COPD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the first genetic investigations of human populations authors have used classical genetic markers such as those of ABO blood groups, the PI system of alpha 1 antitrypsin, HLA Loci, Rhesus system and particularly those of immunoglobulin GM system known by its unparalleled ability, of a single system, to differentiate human populations (for review see Chaabani, 2002). variant is more present in sub-Saharan subjects than in Europeans (Gaillard et al, 1994;Hayes, 2003). The Indian populations of South America were characterized by the high presence of PIM3 allele.…”
Section: Aat Gene Variants and Their Use In Anthropological Investigamentioning
confidence: 99%